Super high-flux dialyzers improve survival in patients on hemodialysis: a cohort study of the Japanese Society for Dialysis Therapy (JSDT) Renal Data Registry - Masanori Abe; Kan Kikuchi; Eiichiro Kanda; Atsushi Wada; Shigeru Nakai; Norio Hanafusa (Renal Replacement Therapy)
Abstract Background In Japan dialyzers are classified as type I, II, III, IV, or V on the basis of the β 2-microglobulin clearance. In 2023, Type V dialyzers were defined as super high-flux membrane dialyzers. Herein, we investigate the association between dialyzer type and mortality. Methods A cohort study was conducted using the Japanese Society for Dialysis Therapy Renal Data Registry database from 31 December 2017, to 31 December 2019. We enrolled 181,879 patients on hemodialysis who were divided into type I–V groups per the Japanese classification. We assessed the associations of each group with 2-year all-cause mortality using Cox proportional hazard models. Furthermore, propensity score matching analysis was performed. Results By the end of 2019, 34,196 patients (18.8%) had died. The hazard ratio (95% confidence interval) was significantly higher in the type I (1.25 [1.12–1.39]), type II (1.21 [1.13–1.31]), and type III (1.07 [1.02–1.13]) groups and significantly lower in the type V group (0.86 [0.80–0.92] P < 0.0001) than in the IV group as a reference after adjusting for all confounders. The type V group had a significantly lower adjusted mortality risk regardless of Kt/V and was robust in several sensitivity analyses. Furthermore, the findings remained significant after propensity score matching. Conclusions This observational study revealed that hemodialysis performed using super high-flux dialyzers may reduce mortality rates regardless of Kt/V. However, to establish the efficacy of super high-flux dialyzers in improving outcomes, randomized controlled trials should be conducted. Trial registration number: UMIN000018641.